Ethnoveterinary Pharmacology: Knowledge Identification of Sukarame Society, Carita, Pandeglang, Banten - Rizhal Hendi Ristanto; Lia Junita Harahap; Elsa Lisanti (UNIVERSITAS NEGERI PADANG, 2019)
The use of chemical medicine in livestock soared. The price of expensive chemical medicine does not discourage people from turning to herbal medicines. The purpose of this study is to determine the level of public knowledge of ethnoveterinary pharmacology and diversity of herbal medicines in the village of Sukarame. This research is quantitative descriptive. Data was collected through observation, semi-structured interviews and identification. The sample in this study was the people in Sukarame village and the types of herbal medicines in Sukarame village. Data from the community was obtained through interviews and observations with the Purposive Sampling technique and data on the type of ethnoverinary obtained from identification. The results showed that public knowledge about ethnoveterinary pharmacology obtained an average score of 55%. The informants who provided data were men at 71% of the total informants. The types of herbal medicines used by the public are Zingiber officinale, Curcuma domestica, Physalis angulata, Piper betle.